Effect of age of a sorghum-sudangrass hybrid on its allelopathic action - Marchi,G. (2008)
Hybrids of Sorghum sudanensis (sudangrass) and Sorghum bicolor genotypes can produce high amounts of biomass, sorgoleone (a long chain hydroquinone), and other phytotoxic substances. Shoots and roots of a sorghum-sudangrass hybrid (cv. Trudan 8) were collected 10, 20, 30, 40, and 50 days after emergence. Four concentrations of aqueous extracts from the shoots and roots (0, 0.4, 2, and 10 g L-1, w/v) were used to treat seeds of lettuce (Lactuca sativa), tomato (Lycopersicum sculentum), purslane (Portulaca oleracea), and pigweed (Amaranthus retroflexus). Seed germination of lettuce, tomato, and pigweed was inhibited by extracts from sorghum-sudangrass shoots at 10 g L-1 when made from sorghum-sudangrass plants 20 days or less in age. Seed germination of purslane was not inhibited by any sorghum-sudangrass extract. Growth of the four species evaluated were systematically inhibited when treated with 10 g L-1 extracts from sorghum-sudangrass shoots harvested up to 10 days after emergence.